Applications of satellite remote sensing technology in health - current situation and enlightenment: a review - Mile LIN; Qianhang XIA; Peng XIE; Zhongyue HUANG; Wuqi QIU; Ayan MAO; Yujie YANG (Editorial Office of Chinese Journal of Public Health, 2024)
Satellite remote sensing technology has been widely applied in various fields due to its efficient data acquisition speed, short period and significant benefit ratio. This article summarizes and analyzes the application of satellite remote sensing technology in the field of health at home and abroad by searching the relevant literature in recent years. From epidemiology, environmental health, medical and health management to public health emergency response, satellite remote sensing technology has shown strong application potential in the field of health. It is recommended to draw on international experience and further expand the application scope of satellite remote sensing technology in China's health field, including expanding the scope of epidemic monitoring, establishing the relationship between environmental factors and health outcomes, and promoting cross-application research in various fields. This will provide more comprehensive and accurate data support for the high-quality development of China's health and wellness initiatives.